PERTANGGUNGJAWABAN HUKUM DOKTER DALAM MENJALANKAN PROFESIONALISME PELAYANAN KESEHATAN TERHADAP PASIEN PESERTA BADAN PENYELENGGARAN JAMINAN SOSIAL KESEHATAN (BPJS KESEHATAN) - Paralam Sinambela (2024)
The provisions of legal norms regarding the relationship between doctors and BPJS Health patients in health services provide a broad perspective, and Law Number 17 of 2023 concerning Health as a replacement for several previous laws in the health sector, provides reforms for Medical Personnel, Health Personnel in general and doctors, especially in health services. This legal research aims to analyze legal norms or provisions regarding the legal responsibility of doctors in carrying out professional health services for patients participating in BPJS Health. The legal research method used in writing this thesis is a normative juridical research method, with a statutory approach and a conceptual approach. The nature of this legal research is prescriptive analytical, by means of qualitative analysis this research uses primary, secondary and tertiary data sources/legal materials used. Data/legal material processing activities begin with collection, analysis and presentation, until they are formulated and presented systematically and descriptively according to each subject matter. The research results show that the legal responsibility of doctors in providing health services to patients participating in BPJS Health begins with supporting the professionalism of Medical Personnel (Doctors) which is implemented by enforcing professional discipline, if there is a violation of malpractice then it is imposed as a Professional Discipline sanction by the Council, and can still be submitted by the patient and his family for civil and criminal charges. And the consequences of ethical violations by doctors can also result in civil or criminal charges if the patient or their family files a lawsuit after receiving a recommendation from the Assembly.